Measurements of particle number mixing ratio with aircraft-borne Optical Particle Counter - Masaharu Watanabe; Yasunobu Iwasaka; Masahiro Nagatani; Hiroshi Nakata; Sadamu Yamagata; Yayoi Inomata; Tetsu Sakai (National Institute of Polar Research, 2002)
Particle number mixing ratios of tropospheric and stratosphenc aerosols were observed in the Arctic Airborne Measurement Program 1998 (AAMP 98) using an Optical Particle Counter onboard a sub-sonic aircraft, the Gulfstream II (G-11) in March 1998. The observational results showed horizontally homogeneous distributions of particle number mixing ratio at the cruise altitude (about 12 km). On the other hand, distinct size-number distributions were found at some points on the flight paths, which suggest that effects of the warm conveyor belts appeared eastward of trough of atmospheric pressure. The characteristics of observed particle size-number distributions are discussed with isentropic backward trajectory analyses and geopotential maps.